The Role of significant others in the utilization of traditional orthopaedic services in Kwara State, Nigeria. (2016)
Orthopaedic injuries contribute to most musculo-skeletal health challenges in developing societies partly due to increasing rate of technological advancement and its associated consequences. Despite the little recognition experienced, traditional orthopaedic service due to the 'severity of most orthopaedic injuries which sometimes 'left patients incapacitated, decision making regarding treatment is sometimes determined by significant others and has implication for patients well being. This forms the focuss of this paper which is hinged on the health belief model as framework for explanation. Both qualitative and quantitative methods were used to elicit data. Questionnaire was administered to 357 randomly selected orthopaedic patients, while In-depth Interview (IDI) was conducted with 7patients and 14 practitioners. Findings revealed that majority of the patients (73.1%) belonged to the active age group (21-60 years); were males (74.5%) who engaged in occupations that predisposed them to orthopaedic injuries. Referral was mainly effected by family members (43:2%), former TOSP's patients (35.4%), friends (13.0%), and members of practitioners' ethnic groups (8.0%) who made these decisions because they were privy to effective treatment offered by the TOSPs. Intensive capacity building and collaboration with western practitioners was recommended for improved delivery of orthopaedic care.